Sistem Informasi E-Learning Untuk Pembelajaran Secara Daring Study Kasus Pada SMK HS Agung - Iis Suryani (Prosiding Sains dan Teknologi, 2022)
E-learning is one of the developments in the use of information technology in the field of education, where e-learning changes the conventional education system into digital form. System Development Life Cycle (SDLC) in systems engineering and software engineering is the process of creating and modifying systems and the models and methodologies used to develop these systems. The results of the implementation of the e-learning system show convenience for students where there is a student data processing menu which is further divided into student input processes and teacher input where in the data input process students and teachers get access to providing material, students learn remotely and explain e-learning can help the distance teaching process, this makes the implementation results according to the existing background. The design of the e-learning system can be applied at SMK HS Agung so that it can reduce the potential for absent students and make reporting easier and can be accessed easily, quickly and accurately. Implementation testing can help teachers and schools in conducting distance learning. The e-learning system can make it easier for students and students to take part in distance learning. Keywords: E-Learning, System Development Life Cycle, SMK HS Agung